Neurological Manifestations of COVID-19 (SARS-CoV-2): A Review - Ahmed, Muhammad Umer; Hanif, Muhammad; Ali, Mukarram Jamat; Haider, Muhammad Adnan; Kherani, Danish; Memon, Gul Muhammad; Karim, Amin H.; Sattar, Abdul (Frontiers in Neurology, 2020)
BACKGROUND Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been associated with many neurological symptoms but there is a little evidence based published material on the neurological manifestations of COVID-19. The purpose of the article is to review the spectrum of the various neurological manifestations and underlying associated pathophysiology in COVID-19 patients. METHOD We conducted a review of the various case reports and retrospective clinical studies published on the neurological manifestations, associated literature and related pathophysiology of COVID-19 using PUBMED and subsequent proceedings. A total of 105 articles were thoroughly reviewed in order to highlight the plausible spectrum of neurological manifestations of COVID 19 as illustrated in Table 1 below. Every article was either based on descriptive analysis, clinical scenarios, correspondence and editorials emphasizing the neurological manifestations either directly or indirectly. We then tried to highlight the significant plausible manifestations and complications that could be related to the pandemic. With little known about the dynamics and the presentation spectrum of the virus apart from the respiratory symptoms, this area needs further consideration. CONCLUSION The neurological manifestations associated with COVID-19 such as Encephalitis, Meningitis and Guillain Barre Syndrome (GBS) are of great concern. But in the presence of life threatening abnormal vitals in severely ill COVID-19 patients these are not usually underscored. There is a need of the hour to diagnose these manifestations at earliest to limit long term sequelae.